MANAGEMENT OF ULCERATIVE ORAL LICHEN PLANUS PREDISPOSED BY PSYCHOLOGICAL STRESS - Rina Kartika Sari; Kus Harijanti; Adiastuti Endah P; Hening Tuti H (FKG Unlam, 2022)
Background: Oral lichen planus (OLP) is a chronic inflammatory autoimmune oral mucosa disease. The ulcerative type of OLP presents as erythematous ulceration with mucosal erosions surrounding whitish striae. The aetiology of OLP is unknown, but can be predisposed by psychological factors. Purpose: Reporting ulcerative oral lichen planus predisposed by psychological stress. Case: A 36 years old woman complained very painful ulcer in the right buccal mucosa and a grey-purple lower lip lesion for a year. It had been treated with topical corticosteroids, antibiotics, tretinoin, and vitamins but did not heal. Extraoral examination on the lower vermillion showed bluish-purple macules, diffuse and irregular borders, rough and painful. Intraoral examination in the right buccal mucosa showed an irregular yellowish-white ulcer with an erythematous area and white striae. Case Management: Screening for psychological stress by DASS 42 showed moderate stress and severe anxiety. Autofluorescence examination showed no malignant transformation sign. A complete blood count test showed low neutrophil and lymphocyte count. ANA test was normal. Systemic Methyl Prednisolone 8 mg was prescribed 2 tabs twice a day and tapered off after the lesion resolved within 1 week. Supportive treatments include Benzydamine HCl and multivitamins. Discussion: Stress, anxiety, and depression were possible factors of OLP mediated by the Hypothalamic-pituitary-adrenal (HPA) axis system and the Sympathetic-adrenal-medullary (SAM) system. Specific mechanisms are mediated by Antigen-specific CD8+ (CTLs) that are activated with the help of CD4+ T-cells. Non-specific mechanism mediated by MMP-9 activation. They led to the apoptosis of keratinocytes. Systemic corticosteroids are an important treatment for oral lichen planus that do not responded to topical steroids. Conclusion: Oral Lichen Planus is a chronic inflammatory disease that affects the oral mucosa and can be predisposed by psychological stress. Corticosteroid is very effective to treat oral lichen planus, especially the erosive-ulcerative type. Keywords: Oral Lichen Planus, Psychological Stress, Ulcerative